2020
DOI: 10.3892/ijmm.2020.4565
|View full text |Cite
|
Sign up to set email alerts
|

TGF‑β1 induces CREB1‑mediated miR‑1290 upregulation to antagonize lung fibrosis via Napsin�A

Abstract: The pathologic mechanisms of pulmonary fibrosis (PF), one of the most common chronic pulmonary diseases, remain unclear. Napsin A is an aspartic proteinase that has been regarded as a hallmark of pulmonary adenocarcinoma. The present study aimed to investigate the specific function and molecular mechanisms of Napsin A in PF from the perspective of microRNA (miRNA or miR) regulation. In the present study, it was found that miR-1290 downregulated the expression of Napsin A by binding to its 3'-UTR. Cell viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, miR-1290 was elevated in peripheral blood dendritic cells from chronic rhinosinusitis patients with nasal polyps [112] and in the duodenal mucosa of coeliac patients [113]. MiR-1290 expression was also higher in plasma from patients with pulmonary fibrosis and it was able to directly target Napsin A proteinase to modulate cell proliferation and TGF-β1-induced fibrosis [114]. On the other hand, miR-1290 expression was decreased in tissue samples from patients with oral submucous fibrosis compared with normal mucosa [115].…”
Section: The Role Of Mir-1290 In Non-neoplastic Diseasesmentioning
confidence: 99%
“…Furthermore, miR-1290 was elevated in peripheral blood dendritic cells from chronic rhinosinusitis patients with nasal polyps [112] and in the duodenal mucosa of coeliac patients [113]. MiR-1290 expression was also higher in plasma from patients with pulmonary fibrosis and it was able to directly target Napsin A proteinase to modulate cell proliferation and TGF-β1-induced fibrosis [114]. On the other hand, miR-1290 expression was decreased in tissue samples from patients with oral submucous fibrosis compared with normal mucosa [115].…”
Section: The Role Of Mir-1290 In Non-neoplastic Diseasesmentioning
confidence: 99%
“…Downregulation of Nap‐A is a hallmark of lung adenocarcinoma and pulmonary fibrosis 114 . Overexpression of miR‐1290 in A549 cells not only significantly induces cell proliferation but also by downregulation of Nap‐A increases the level of fibrosis marker proteins (Collagen I, α‑SMA, and TGF‑β1) 88 …”
Section: Potential Roles Of Mir‐1290 In Cancer Prognosis and Treatmen...mentioning
confidence: 99%
“…Since then, several studies have shown that Napsin A can also be expressed in other tumor types [7,11,12]. For example, immunohistochemical Napsin A positivity was found in 0%-52% of clear cell renal cell carcinomas [6,[13][14][15][16][17][18][19][20][21][22], 72%-97% of papillary renal cell carcinomas [6,13,14,[16][17][18][20][21][22], 0%-48% of thyroid tumors [10,11,16,18,19,23,24], 69%-100% of clear cell carcinomas of the ovary [7,19,[25][26][27][28][29][30][31][32] and 0%-9% of cholangiocarcinomas [12,19,33,34]. Partially conflicting results with respect to positivity rates between these studies may be due to the use of different antibodies, the use of different immunostaining protocols as well as different criteria to determine positivity in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was demonstrated that Napsin A is regulated by thyroid transcription factor 1 (TTF1), a diagnostic marker in lung cancer [ 3 ]. A recent study has shown that downregulation of Napsin A promotes TGF-ß induced cell proliferation in lung adenocarcinoma cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%